Total robotic radical rectal resection with da Vinci Xi system: single docking, single phase technique. Issue 4 (3rd February 2016) - Tamhankar, Anup Sunil; Jatal, Sudhir; Saklani, Avanish
Abstract: Objective: This study aims to assess the advantages of Da Vinci Xi system in rectal cancer surgery. It also assesses the initial oncological outcomes after rectal resection with this system from a tertiary cancer center in India. Introduction: Robotic rectal surgery has distinct advantages over laparoscopy. Total robotic resection is increasing following the evolution of hybrid technology. The latest Da Vinci Xi system (Intuitive Surgical, Sunnyvale, USA) is enabled with newer features to make total robotic resection possible with single docking and single phase. Methods and results: Thirty‐six patients underwent total robotic resection in a single phase and single docking. We used newer port positions in a straight line. Median distance from the anal verge was 4.5 cm. Median robotic docking time and robotic procedure time were 9 and 280 min, respectively. Median blood loss was 100 mL. One patient needed conversion to an open approach due to advanced disease. Circumferential resection margin and longitudinal resection margins were uninvolved in all other patients. Median lymph node yield was 10. Median post‐operative stay was 7 days. There were no intra‐operative adverse events. Conclusion: The latest Da Vinci Xi system has made total robotic rectal surgery feasible in single docking and single phase. With the new system, four arm total robotic rectal surgery may replace the hybrid technique of laparoscopic and robotic surgery for rectal malignancies. The learning curve for the new system appears to be shorter than anticipated. Early perioperative and oncological outcomes of total robotic rectal surgery with the new system are promising. Copyright © 2016 John Wiley & Sons, Ltd.